2003
DOI: 10.1016/s1078-5884(03)00344-7
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin and Triclosan but not Silver is Effective in Preventing Bacterial Infection of Vascular Dacron Graft Material

Abstract: Silver coating failed to prevent graft infection material. A potential antimicrobial property was evident for Triclosan whereas Rifampin-bonded grafts exhibit a significantly reduced infection rate. Thus, silver-coated vascular grafts cannot ensure protection from vascular graft infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 32 publications
2
51
0
2
Order By: Relevance
“…Coatings containing combinations of antibiotics and antiseptics like minocycline and rifampin or chlorohexidin and silver-sulfadiazine have been applied to the internal and external surface of catheters. In several studies these antimicrobial coated catheters were compared to non-coated catheters, and a reduction of catheter colonization and catheter related blood-stream infections were found [66][67][68]. The antimicrobial effect of antibiotics containing coatings was more pronounced than for the antiseptic coatings.…”
Section: Antibiotic Releasing Coatingsmentioning
confidence: 99%
“…Coatings containing combinations of antibiotics and antiseptics like minocycline and rifampin or chlorohexidin and silver-sulfadiazine have been applied to the internal and external surface of catheters. In several studies these antimicrobial coated catheters were compared to non-coated catheters, and a reduction of catheter colonization and catheter related blood-stream infections were found [66][67][68]. The antimicrobial effect of antibiotics containing coatings was more pronounced than for the antiseptic coatings.…”
Section: Antibiotic Releasing Coatingsmentioning
confidence: 99%
“…''Silver coating" of vascular prostheses was also performed for its antimicrobial effect. Goeau et al [11] and Hernandez et al [12] showed that rifampicin bonding was superior to silver coating or triclosan of vascular prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…В неко-торых работах предполагается, что миграция ионов из материала протеза в окружающие ткани вообще может не происходить [21]. Теоретические рассуждения по этому вопросу иллюстрируются данными исследований, прове-денными in vitro [34], а также in vivo на мышах [35] и сви-ньях [36]. Ряд авторов [22,36,37] приводят данные, свиде-тельствующие о том, что импрегнированные серебром протезы уступают по эффективности пропитанным анти-биотиком или антисептиком.…”
Section: Discussionunclassified